Ambient air pollution exposure association with diabetes prevalence and glycosylated hemoglobin (HbA1c) levels in China. Cross-sectional analysis from the WHO study of AGEing and adult health wave 1. Issue 10 (23rd August 2020) - Elbarbary, Mona; Honda, Trenton; Morgan, Geoffrey; Kelly, Patrick; Guo, Yuming; Negin, Joel
Abstract: Over the past decades, air pollution has become one of the critical environmental health issues in China. The present study aimed to evaluate links between ambient air pollution and the prevalence of type 2 diabetes mellitus (T2DM) and the levels of glycosylated hemoglobin (HbA1c). A multilevel linear and logistic regression was used to assess these associations among 7, 770 participants aged ≥50 years from the WHO Study on global AGEing and adult health (SAGE) in China in 2007-2010. The average exposure to each of pollutants (particulate matter with an aerodynamic diameter of ≤10 μm/≤2.5 μm/≤1 μm [PM10 /PM2.5 /PM1 ] and nitrogen dioxide [NO2 ]) was estimated using a satellite-based spatial statistical model. In logistic models, a 10 µg/m 3 increase in PM10 and PM2.5 was associated with increased T2DM prevalence (Prevalence Odds Ratio, POR: 1.27; 95% CI: 1.11, 1.45 and POR: 1.23; 95% CI: 1.03, 1.46). Similar increments in PM10, PM2.5, PM1 and NO2 were associated with increase in HbA1c levels of 1.8% (95% CI: 1.3, 2.3), 1.3% (95% CI: 1.1, 1.5), 0.7% (95% CI: 0.1, 1.3), and 0.8% (95% CI: 0.4, 1.2), respectively. In a large cohort of older Chinese adults, air pollution was liked to both higher T2DM prevalence and elevated HbA1c levels.